Green tax: A bibliometric analysis - Dias, P.; Santos, I. (Taking on climate change through green taxation, 2023)
In this study the authors provide a bibliometric overview regarding available articles in SCOPUS database about green tax and double dividend. The results show that the theme has recently become more popular, with most articles affiliated with European countries. Regarding the sources of publication, the authors identified that the most influential journals are environmental, resources economics, and energy economics, where most of the articles are published. Finally, through keyword analysis the authors concluded that green tax focus areas are often related to double dividends, sustainable development, environmental fiscal reform and market-based instruments, while double dividend focus areas are related to Environmental tax reform, environmental policy, economic growth, employment, optimal taxation, and carbon tax demonstrating that these are the most influential topics on the subject